LATTICE VALUED ALESHIN TYPE AUTOMATA WITH -MOVES - Jeyanthi, A.; Kalpana, V. (IJRDO -Journal of Computer Science Engineering, 2015)
The extended subset construction of lattice-valued Aleshin type finite automata is introduced, then the equivalences between lattice-valued finite automat , latticevalued deterministic finite automata and lattice-valued finite automata with e-moves are proved. A simple characterization of lattice-valued languages recognized by lattice-valued finite automata is given, then it is proved that the Kleene theorem holds in the frame of lattice-setting. A minimization algorithm of lattice-valued deterministic finite automata is presented. In particular, the role of the distributive law for the truth valued domain of finite automata is analyzed: the distributive law is not necessary to many constructions of lattice-valued finite automata, but it indeed provides some convenience in simply processing lattice-valued finite automata